Analisis Komparatif Kualitas Pelayanan pada Nasabah Pengguna Aplikasi Pegadaian Syariah Digital dan Manual: Studi Kasus Pegadaian Syariah Cabang Kusumanegara - widyawati, Weni; Mahatir, Fahmi Mar’i; prasetyo, priyono puji; asakdiyah, salamatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The background of the problem of this research is a comparison of the quality of service received by customers using the Pegadaian Syariah Digital application and manually at Pegadaian Syariah Kusumanegara Branch Yogyakarta. Customers predominantly use the manual system rather than using the Pegadaian Syariah Digital application, because the system often errors and transaction failures occur. The Pegadaian Syariah Digital application is expected to help customers make smartphone transactions without having to make transactions manually. With this Digital Sharia Pegadaian application, it can meet the needs of customers when transacting without directly attending the Sharia Pegadaian and this application has various features that will be selected when transacting. The formulation of the problem of this study is whether there are differences in service quality for customers using digital and manual sharia pawnshop applications. This research is quantitative research, this type of research is also comparative analysis research, the data source used is primary data. The data collection technique used is a questionnaire with a total sample size of 100 samples which are divided into 50 samples for digital sharia pawnshops and 50 samples for manual ones. The analysis techniques used are validity test, reliability test, mann whitney test, and homogeneity test. The results obtained in this study indicate that there is no significant difference between digital and manual pawnshops.